Late-Onset Pompe's Disease - Teener, James W. (Seminars in Neurology, 2012)
Glycogen storage disease type II, also known as Pompe's disease or acid maltase deficiency, is caused by a deficiency in acid α-glucosidase. Severe enzyme deficiency results in infantile Pompe's disease with multiorgan involvement; a partial deficiency produces a less severe phenotype mainly consisting of a myopathy, with a later age of onset. Treatment is now available with intravenous infusion of recombinant acid α-glucosidase. Such treatment results in marked improvement in patients with infantile Pompe's disease, and modest improvement or stabilization in patients with late-onset Pompe's disease.
Keywords: Pompe's disease; acid maltase deficiency; lysosomal storage disease; glycogen storage disease type II